The Volume and Geochemical Characteristics of Desorption Gases From Wufeng–Longmaxi (O3w-S1l) Shale in the Xishui Area, North Guizhou, China - Shi, Shuyong; Wang, Yunpeng; Sun, Yu; Guo, Huijuan (Frontiers in Earth Science, 2022)
The Upper Ordovician-Lower Silurian Wufeng-Longmaxi (O3w-S1l) shale is widely distributed in the Xishui Area, North Guizhou, China. However, the potential and characteristics of shale gases in the Xishui Area are not well evaluated, which has limited the exploration of shale gas in this area. In this study, we collected 14 fresh core samples of Wufeng-Longmaxi Formations from Well XK-3 and conducted gas-desorption experiments to evaluate the potential of shale gas resources in the Xishui Area. After analyzing the chemical and isotopic composition of desorption gases, the origin and genesis of the shale gas were systematically studied. Our results show that the volume of desorption gases varies from 2.14m3/t to 6.01m3/t, with a mean value of 4.12m3/t, showing great potential for shale gas in this area. The positive correlation between TOC (Total Organic Carbon) and gas-adsorption volume indicates organic matter provides the main pore volume for shale gas preservation. The desorption gases are very dry, which are mainly composed of methane (99.64%-99.74%) with a very low content of ethane, and no nitrogen, carbon dioxide, and hydrogen sulfide are detected. Based on geochemical diagrams, the desorption gases are identified as oil-associated thermogenic gases. The carbon isotopic values of methane and ethane display reversal distribution, due to the mixing of primary gases from kerogen cracking and the secondary gases from retained-oil cracking and the further possible cracking of heavy gaseous hydrocarbons (C3H8 - C5H12) at higher thermal maturity (Ro > 2.00%). After comparing with Jiaoshiba, Changning, Weiyuan, and Dingshan areas, the carbon isotopic values of shale gases of Wufeng-Longmaxi shale also show different features at different areas, which are mainly controlled by the thermal maturity levels of the shale.